PENGGUNAAN PENDEKATAN PEMBELAJARAN INOVATIF BERBASIS DEEP DIALOGUE/CRITICAL THINKING TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU - Baziduhu Laia (Jurnal Education and Development, 2020)
This study aims to determine the increase in student learning outcomes after an innovative learning approach based on deep dialogue / critical thinking in Integrated Social Studies subjects with the material of the Indonesian economic system in class VIII SMP Negeri 2 Toma. The instruments used were: (1) observation sheets, (2) test learning outcomes, (3) photo documentation. Learning outcome tests are used to see an increase in student learning outcomes. The subjects in this study were class VIII-A SMP Negeri 2 Toma. From the results of research with a learning approach based on deep dialogue / critical thinking, this can be seen in the research of each cycle. (1) the average student learning outcomes in the first cycle only reached 71, while in the second cycle the average student learning outcomes increased to 86.12. (2) The result of teacher observations in the first cycle of the first meeting was 75%. While at the second meeting it was 82.69%. In the second cycle the first meeting was 88.46%. While at the second meeting it was 96.15%. Based on the results of this study, it can be concluded that the use of innovative learning approaches based on deep dialogue / critical thinking can improve student learning outcomes in Integrated Social Studies subjects. For this reason, it suggests suggestions (1) The teacher who applies it applies the appropriate learning approach in accordance with the material being applied. (2) The teacher can master various learning approaches so that they can be applied during the learning process (3) Develop further research with a longer time planning so that the research results obtained are maximized and effective (4) the results of this study are used as a basis for development for research Furthermore.